Technical manual on mechanized rice seeder utilization for enhancing productivity and quality in rice seed production in Cambodia - Pin, S.; Then, R. (International Rice Research Institute, 2024)
Over the last three decades, many rice farmers in Cambodia have adopted broadcast direct seeding as a solution to address labor shortage. However, this shift has often resulted in lower yields due to sub-optimal agronomic practices. Seed producers also face the same constraints. The problem of seed producers however, exacerbates the already limited supply of quality seeds for farmers. Mechanized direct seeding in rows, combined with improved agronomy, has been shown to enhance rice yields. Cambodian rice farmers could increase their yields by up to 0.9 tons per hectare. It also has potential for seed producers that are already doing broadcast seeding. There is a need to improved practices and inform the seed producers so that they can harness the benefits of mechanized direct seeding for their production.